Synthesis and characterization of novel magnetically separable CoFe2O4/CeO2nanocomposite photocatalysts - Natda Wetchakun (2018)
The novel CoFe2O4/CeO2nanocomposite materials were successfully synthesized by coupling a homogeneous precipitation method with hydrothermal method. The mole ratios of CoFe2O4:CeO2in this study were varied as follows: 0.2:0.8, 0.4:0.6, 0.5:0.5, 0.6:0.4 and 0.8:0.2. The obtained CoFe2O4/CeO2nanocomposites were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), and Brunauer, Emmett and Teller (BET) techniques. The magnetic properties of CoFe2O4and CoFe2O4/CeO2samples were determined by using a vibrating sample magnetometer (VSM) at room temperature. The characteristic results of CoFe2O4/CeO2nanocomposite samples indicated that they had a cubic structure. All CoFe2O4/CeO2composite particles existed as spherical-like shape and showed high specific surface area in the range of 98-180 m2g-1. The saturation magnetization (Ms) of 0.4CoFe2O4:0.6CeO2nanocomposite was 25.375 emu g-1. The CoFe2O4/CeO2nanocomposite was expected to use as a magnetic photocatalyst for degrading some organic compounds. © 2013 Elsevier B.V.